Constitutional delay of puberty: presentation and inheritance pattern in 48 familial cases. Issue 1 (December 2016) - Winter, Sarah; Ousidhoum, Aldjia; McElreavey, Kenneth; Brauner, Raja
Abstract Background The mechanism that initiates the onset of puberty is largely unknown but the age of onset is mainly under genetic control and influenced by environmental factors including nutrition. Familial forms of constitutional delay of puberty (CDP) suggest the involvement of genetic factors. The purpose of this study is to describe the presentation and the mode of inheritance of CDP in a series of familial cases. Methods A retrospective, single center study was carried out over 10 years on 48 probands (14 girls and 34 boys) from 48 families seen for CDP with a familial component. Results Of the 48 probands, 46 (96 %) had at least one affected 1st degree relatives and 2 (4 %, 2 boys) had only 2nd degree relatives affected. In girls, 11 families (79 %) exhibited exclusive maternal inheritance, 1 (7 %) paternal inheritance and 2 (14 %) both maternal and paternal inheritance. In boys, 14 families (41 %) exhibited exclusive maternal inheritance, 12 (35 %) paternal inheritance and 8 (24 %) both maternal and paternal inheritance. In the boys with bilineal inheritance, the ages at onset of puberty (16 ± 1.41 years) and at evaluation (16.05 ± 2.47 years) were higher than in those with unilineal inheritance (15.25 ± 0.35 and 15.1 ± 0.42 years respectively), but the difference was not significant. Conclusions In girls exclusive maternal inheritance seems to be the major mode of inheritance whereas for boys the mode of inheritance was almost equally maternal, paternal or bilineal. Clinical phenotype of boys with bilineal inheritance seems to be more severe, but the difference did not reach statistical significance, perhaps because of the small sample size. This greater severity of the phenotype in boys with bilineal inheritance is likely due to inheriting different puberty timing genes from each parent. Future research should be directed at identifying such genes.